Service user involvement in healthcare service development: knowledge, representativeness & the 'professional' user - El Enany, Nellie (2013)
Policy makers have increasingly regarded user involvement as an important dimension of service development. Current government policy advocates the involvement of service users in healthcare service development across all levels of an organisation, ranging from the level of individual service user to the development and improvement of health services (DoH 1992, 1999, 2001a, 2001b, 2003a, 2003b, 2004, 2005a, 2007a, 2007b, 201Oa, 201Ob, 2011, 2012). This has manifested in the creation of a number of public and patient involvement initiatives including Patient Advocacy and Liaison Services (PALS), Locals Involvement Networks (LINks), Patients Forums and more recently Healthwatch Organisations. User movements and policy pressures have also led to the formation of user led groups pushing for changes in health and social care. However, these groups often operate on the margins, and as such, lack the legitimacy to work alongside professionals in service development and improvement.